Understanding urbanism. - (:unkn) unknown (Palgrave Macmillan, 2020)
Understanding Urbanism presents built environment students with the latest approaches to studying urbanism. The book is written in an accessible and easy-to-understand format by leading urban academics and practitioners with decades of teaching and practical experience. As students move through the chapters, they will develop a critical understanding of the different ways architects, urban and social planners, urban designers, heritage professionals, engineers and other built environment professionals design our cities. Importantly, the book shows how and why the built environment professional of the future will need to work within the Indigenous context of cities in countries like Australia, New Zealand, the United States and Canada.
Keywords: Urbanismus; Stadtplanung; Stadtsystem; Stadtgrundriss; Stadtverkehr; Stadtökonomie; Stadtökologie; Stadtgestaltung; Multikulturelle Gesellschaft; Digitalisierung; Smart City; Stadtpolitik; Stadttheorie; Lehrbuch